Proses Pembelajaran Terhadap Anak-Anak Berkebutuhan Khusus di SLB SD Tunas Harapan Mandiri - Gulo, Santa; Lusia, Yunarti; Hulu, Anna; Sewi, Yolanda; Hutasoit, Loripa; Gaol, Herna Lumban; Sihombing, Elisabeth; Sinuraya, Delviana (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Education in Indonesia provides Special Schools (SLB) for children with special needs. With inclusive education for children with special needs, it is hoped that a society that is more inclusive, empathetic and respectful of diversity can be created. Every child has the right to receive a decent education without exception. There will definitely be challenges for teachers in teaching and educating IMR children in the learning process, both from cognitive weaknesses and behavioral problems. There are still many people, even prospective teachers, who still don't know and understand how the learning process for AKB children is in SLB. This is the reason for conducting research using observation and interview methods to see the progress of AKB children in the learning process. Through these observations, it is known that AKB children find it very difficult to follow the learning process, even though they apparently have the ability and opportunity to learn better. Which means that SLB provides changes for the better to every AKB child, both in terms of affective, cognitive and psychomotor. Teachers provide learning materials and methods adapted to the needs and circumstances of the students. Therefore, the learning system at SLB is not much different from the learning system at other schools where both have learning outcomes and goals that need to be achieved in improving the quality of students or children with special needs.